Emancipatory education: Leónidas Proaño's Education for freedom - Oviedo Oviedo, Alexis (2019)
Education is a powerful instrument to reproduce the dominant hegemony in the new generations, or being an instrument of liberation of the poor segments of society. This article shows how these processes of hegemonic reproduction and educational proposals are developed so that education is not a reproductive instrument, but an effective tool for liberation. Both roles are seen in the Ecuadorian reality, from the influence of the Catholic Church in the consolidation of the dominant axiology, to the attempts developed by the citizen revolution governmet to include religion in the public school.